Evidence for a non-orthostatic origin of orthostatic tremor. Issue 3 (1st March 1999) - Boroojerdi, B; Ferbert, A; Foltys, H; Kosinski, C M; Noth, J; Schwarz, M
Abstract : OBJECTIVES: Orthostatic tremor was first described by Heilman in 1984. It usually occurs in the legs during stance and decreases markedly during sitting or walking. The aim of this study was to determine if orthostatic tremor is invariably associated with the orthostatic and weight bearing conditions in the arms and legs, and to investigate the features of orthostatic tremor under different levels of peripheral loading. METHODS: Multichannel surface EMG recordings were obtained under different conditions (body posture and peripheral loading) from the proximal arm and leg muscles of seven patients fulfilling the clinical and electrophysiological criteria of orthostatic tremor. RESULTS: In weight bearing positions (stance; weight bearing on the hands on all fours), all patients showed 13 Hz-16 Hz tremor activity, predominantly in the active limb. No tremor activity could be found in a supine position with muscles at rest. Isometric contraction of the limbs in the supine position led to synchronous 13 Hz-16 Hz rhythmic activity in five patients. No tremor was seen when the subjects were suspended in a harness with relaxed legs. Isometric contraction of the legs in this position produced tremor in two patients. A stepwise reduction of the body weight by a harness reduced the tremor activity. Additional loading (10 kg-20 kg) during stance led to an increase in tremor amplitude, but tremor frequency remained unchanged. CONCLUSIONS: Orthostatic tremor is invariably present during stance or other weight bearing positions. It is not, however, always associated with orthostasis. In at least some patients it can be classified as an orthostasis independent action tremor. The failure of peripheral loading to modify tremor frequency indicates that orthostatic tremor may have a central, rather than a peripheral, origin.